EFEKTIVITAS FACEBOOK DALAM MENYEBARKAN INFORMASI PADA KOMUNITAS SOLO LAST FRIDAY RIDE - Sari, Maharani Mutiara (JURNAL KOMUNITAS, 2017)
The aims of this research is to explain the effectiveness of the use of facebook as the media in disseminating information on Solo Last Friday Ride Community. ThisResearch belongs to a descriptive quantitative study, the data obtained used questionnaires methods. This research used random sampling purposive sampling, the sample of the reseach is members of the community, it’s about 10,000 members. Moreover sampling used a formula developed by Slovin with significant levels of 10%. It obtained a value of samples with N = 10,000, with a 10% error level obtained a sample value 100 members. This research was descriptive quantitative analysis gives an overview of the condition of the object without making a comparison. Analysis of univariate analysis was used by calculating the frequency distribution of each variable are examined. Base on research and discussion, it can be concluded that the effectiveness of Community Facebook account Solo Last Friday Ride Community in spreading information is categorized as effective. This is due to the fact that of all the variableused to measure the effectiveness of facebook on Solo Last Friday Ride shows the percentage above 80%. Facebook is still regarded as an effective means for community members Solo Last Friday Ride, because the content of what is posted by assessed the informationsubmitted to the Member that is clear, the update and in accordance with the contents of the message.